Evaluation of coal pond ash and quarry dust mix for pavement application - Mogili, Sudhakar; Mudavath, Heeralal; Kapuganti, Chitti Babu; Goray, Nawin Kumar (Engineering and Applied Science Research, 2024)
The depletion of high-quality natural resources such as soils and aggregates emphasize the necessity of incorporating alternative sustainable materials in road construction. Utilizing these waste materials not only addresses the challenge of their safe disposal but also contributes to sustainable road infrastructure development. The present work examined the potential of coal pond ash (Class F) modified with cementitious material like lime (L) and quarry dust (Q) in the subbase layer of flexible pavements. Through a series of tests including compaction, unconfined compression strength, durability assessment, and repeated load triaxial testing, it was determined that a mixture containing lime modified pond ash (70% P + 10% L) along with quarry dust of 20% exhibited the desired strength and durability characteristics required for subbase material in flexible pavement construction. Also, the proposed mixture demonstrated higher resilient modulus (MR) than the traditional subbase layer (GSB). Further, the performance of pavement structure with the proposed mix by using KENLAYER analysis showed service life ratio (SLR) values of 1.175 for fatigue and 1.143 for rutting criteria in compared with GSB. From these findings it is suggested that the proposed mix offers a viable and sustainable solution for the road applications.